The Relationship Between Cybersecurity and Public Trust in Digital Services: A Literature Review - Cory Kartika Putri; Ahmad Nuradi; Wachid Maulana; Andi Adri Agus; agus eko setyawan; Pandri Zulfikar (International Journal of Business and Quality Research, 2026)
The rapid expansion of digital services has transformed how societies interact with public and private institutions. However, the increasing prevalence of cyber threats has raised concerns regarding data security and privacy, directly influencing public trust. This study aims to examine the relationship between cybersecurity and public trust in digital services through a systematic literature review. The findings indicate that cybersecurity effectiveness plays a critical role in shaping user confidence, particularly in contexts involving sensitive data such as digital payments and online banking. Perceived security, awareness of cyber risks, and institutional responses to cyber incidents significantly affect trust formation and retention. Moreover, trust is not solely dependent on technical security measures but also on transparency, communication, and governance frameworks. The study also highlights that cyber incidents can severely damage trust, requiring structured recovery mechanisms to rebuild confidence. Overall, the literature suggests a strong positive relationship between cybersecurity and public trust, where improved security infrastructure and user awareness enhance trust in digital platforms. This paper contributes to the growing discourse on digital governance by emphasizing the need for integrated cybersecurity strategies to sustain public trust in digital ecosystems. Keywords: cybersecurity, digital trust, public trust, digital services